Environmental enrichment enhances anesthetic actions in rat amygdala hippocampal circuits in vitro - Onishi, Kenta; Sasaki, Rika; Hirota, Koki; Takazawa, Tomonori (Frontiers in Pharmacology, 2025)
IntroductionEnvironmental enrichment enhances hippocampal synaptic plasticity, yet its influence on anesthetic action remains poorly understood. This study tested the hypothesis that enriched environment (EE) rearing modifies the inhibitory effects of propofol and desflurane on synaptic transmission within a novel limbic circuit slice preparation preserving amygdala–hippocampal connections.MethodsSlices were obtained from male rats reared in either a standard environment (SE) or an EE. Electrophysiological recordings measured population spike (PS) amplitudes in CA1 pyramidal neurons.ResultsIn slices from EE rats, the inhibitory effects of both anesthetics on PS amplitude were markedly potentiated compared with SE rats. The IC50 of propofol decreased from 3.3 × 10–4 M [IQR: 2.7 × 10–4 −3.5 × 10–4] in SE to 5.4 × 10–5 M [IQR: 5.1 × 10–5 −5.6 × 10–5] in EE (P = 0.002), whereas that of desflurane decreased from 10.4 vol% [IQR: 10.3−11.5] to 6.5 vol% [IQR: 4.8−7.1] (P = 0.002). Potentiation was more pronounced for propofol, which acts primarily through GABA receptors, whereas desflurane, with multiple molecular targets, showed a smaller potency change accompanied by an increased Hill coefficient, suggesting altered receptor binding cooperativity. Recovery of inhibitory tone following stimulus-induced disinhibition was accelerated in EE slices. This effect was most prominent with propofol, for which the recovery time constant decreased from 146.0 s [IQR: 110.6−642.8] in SE to 36.6 s [IQR: 25.5−48.9] in EE (P = 0.008).DiscussionThese findings demonstrate that rearing in an enriched environment enhances anesthetic potency by strengthening GABAergic inhibitory circuits and modifying pharmacological profiles at the network level. This enhancement was most evident for propofol, indicating that environmental factors can significantly influence anesthetic sensitivity within hippocampal circuits. Clinically, an individual’s life history and environment may represent critical yet overlooked determinants of anesthetic requirements. These results highlight the importance of personalized pharmacology in anesthesia and suggest that standardized dosing of GABAergic agents may cause overdose in individuals with enhanced inhibitory function. Overall, this study provides mechanistic insights into how environmental neuroplasticity modulates anesthetic pharmacodynamics, advancing our understanding of interindividual variability in drug response and perioperative safety.